Blue Energy Potential Analysis in the Mediterranean - Nikolaidis, Georgios; Karaolia, Andria; Matsikaris, Anastasios; Nikolaidis, Andreas; Nicolaides, Marios; Georgiou, Georgios C. (Frontiers in Energy Research, 2019)
This paper describes the status of the potential of blue energy in the Mediterranean region, with focus on the region around Cyprus. Previous studies are reviewed, the main findings of the blue energy potential analysis performed in the frame of the MAESTRALE project are presented, and the most promising blue energy sources for the Mediterranean are highlighted. The findings of this report suggest that there is a good exploitability potential of different forms of BE in the Mediterranean. The most highlighted BE form for the Mediterranean region is offshore wind energy. This is also true for Cyprus, where marine biomass follows as the second most promising blue energy form. Marine thermal energy can also be used for heating and cooling. The main physical barrier for the implementation of BE projects is the bathymetry around the island